EFEKTIVITAS BANTUAN BEDAH RUMAH TERHADAP FAKIR MISKIN (Studi di Kecamatan Gu Kabupaten Buton Tengah) - Reni, Reni; Peribadi, Peribadi; Tunda, Amin (Universitas Halu Oleo, 2021)
The purpose of this study was to determine the process of implementing house renovation assistance and its effectiveness for the poor in Kamama Mekar Village and Rahia Village in Gu Subdistrict, Central Buton Regency. The research method used is descriptive qualitative by selecting informants by purposive sampling. The iformants in this study were the Consultant Team in implementing house renovation assistance, the Village Head, the Head of Customs/Hamlet and the Community who received assistance. The results showed the process of implementing house renovations in Kamama Mekar and Rahia villages. First, data collection was carried out by each hamlet head in each village. Second, a location review carried out by each Village Head to ensure the accuracy of the data on the receipt of house renovation assistance. Third, verification of data from the ministry for further action and Fourth, the process of house renovation assistance that is carried out in each hamlet in the village to communities that are eligible for their place of residence in rehab or who areentitled to receive house renovation assistance. After the house renovation assistance processs is carried out, it is seen from the effectiveness as stated by Edy Sutrisno that the effectiveness in dicator consists of First, understanding the program. Where the understanding of this program can be seen to what extent the community can understand these programs. Second, right on target, as stated by Bernard, that effectiveness is a dynamic condition of a series of processes for the implementation of tasks and functions of work in accordance with the objectives and targets of the program policies that have been set, with this conceptual definition a dimension of study is obtained, namely the dimension of program effectiveness. Third, on time in the process of implementing the construction of alivable house renovation program for the community in Kamama Mekar Village and Rahia Village, it has adjusted to the time set by the Central Buton Regency PUPR Service. And Fourth, real change, namely a program seen through the extent to which program activities give an effect or impact before and after the program has made changes to all related aspects.